Microstructure and performance of 1–3 connectivity environmental friendly lead-free BNBK-Portland cement composites - Potong R. (2017)
© 2017 Elsevier Ltd The 1–3 connectivity lead-free piezoelectric composites were produced from the bismuth sodium titanate-bismuth potassium titanate-barium titanate (BNBK) ceramic and Portland cement (PC) by dice-and-fill method. Microstructure and performance of composites were investigated and compared with predicted models. The results indicated that the BNBK ceramic can improve the dielectric, piezoelectric coefficient and thickness electromechanical coupling coefficient properties in composites. At ≈40% BNBK ceramic content is the optimal BNBK content for an acoustic impedance match between composites and concrete. The dielectric constant and piezoelectric coefficient were close to the parallel model. The piezoelectric voltage coefficient of all composites was found to be higher than pure ceramic and the g 33 value were found to be 26.55 × 10 −3 Vm/N and 21.74 × 10 −3 Vm/N for composite with 30% and 70% BNBK contents, respectively. The 1–3 BNBK-PC composites have good compatibility with concrete obtaining good performance for use in smart structures applications.